Insights into the Electrochemical Reduction of 5‐Hydroxymethylfurfural at High Current Densities. Issue 13 (3rd March 2022) - de Luna, Giancosimo Sanghez; Sacco, Adriano; Hernandez, Simelys; Ospitali, Francesca; Albonetti, Stefania; Fornasari, Giuseppe; Benito, Patricia
Abstract: The electrocatalytic reduction of 5‐hydroxymethylfurfural (HMF) is highly selective to 2, 5‐bishydroxymethylfuran (BHMF) at pH=9.2, diluted HMF solutions, and low current densities. In this work, the electrochemical reduction of 0.05 m HMF solutions was investigated in the 5–50 mA cm −2 current density range over an AgCu foam electrocatalyst. The selectivity towards the formation of BHMF or the dimerization depended on the current density, likely due to differences in the electrode potential, and on the reaction time. Operating at current densities of 40–50 mA cm −2 allowed to find a trade‐off between HMF and H2 O activation, achieving 85 % BHMF selectivity and fostering the productivity (0.567 mmol cm −2  h −1 ), though co‐producing H2 . The electrochemical characterization by Tafel slopes and electrochemical impedance spectroscopy indicated that the HMF reduction was kinetically favored in comparison to the hydrogen evolution reaction and that the process was limited by charge transfer. Abstract : BHMF electrosynthesis : The electrocatalytic reduction of 0.05 m 5‐hydroxymethylfurfural (HMF) solutions to 2, 5‐bishydroxymethylfuran (BHMF) is feasible at high current densities over nanostructured AgCu foam electrocatalysts. High BHMF selectivity and productivity values are achieved, suppressing the formation of hydrofuroin by‐product, though co‐producing H2 . The process is fostered in the potential window where HMF reduction is favored and H2 production from the hydrogen evolution reaction is not inhibited.